Pengembangan Media Video Animasi Mitigasi Gempa Bumi Dalam Sub Tema Keadaan Alam Indonesia Untuk Siswa Kelas Vii SMPN 01 Surakarta - Fitriani, Mariska; , Drs. Muhammad Musiyam, M.TP (2017)
Reseach have a purpose (1) develop an interactive learning media in social science study class VII Sub-themes themes natural state of Indonesia, (2) determine efectiveness interactive learning media media in social science study class VII sub-themes natural state of Indonesia, (3) improving student learning outcomes in social science study class VII sub- themes natural state of Indonesia. The research is reseach and development using Sugiyono's develop model. Reseach conducted in junior high school 01 of Surakarta. the sampling using simple random sampling and then, collect data by distributing questionaries need of teachers and student's needs questionaire. Product develop is video animation intructional media are included in social science subject geological condition of the sub-themes Indonesia natutal state. Video has been validated by subject matter expert and media expert. The result of reseach carried there is a significant difference, As evidence by the acquisition of learning outcomes through pre test and post test. after tested by t-test get result sig(2-tailed) 0,000 that Ho refused And H1 accepted, the meaning that there are differences in the result of pre test and post test. Keyword: Reseach and development, video animation, Mitigation, Earthquake